Patients decision factors of alternative medicine purchase: an empirical investigation in Malaysia - Haque, A. K. M. Ahasanul; Chowdhury, Naila Anwar; Kabir, SMH; Yasmin, Farzana; Tarofder, Arun Kumar; MHM, Nazmul (Advanced Scientific Research, 2020)
Alternative Medicine is a mode of therapies and therapeutics used in place of conventional medicines. For the past decades, alternative medicine has made significant contributions to harmonize the human body’s natural healing process. This study examined decision factors such as patient’s attitude, subjective norm, perceived behavioral control, knowledge, and purchase intention to buy alternative medicine in Malaysia. The study was conducted following a quantitative research approach. Primary data were collected through the deployment of self-administered questionnaires from 350 patients in Klang Valley, Malaysia. For the purpose of the study, Exploratory Factor Analysis (EFA) and Structural Equation Modeling (SEM) techniques were performed. Patient’s perceived behavioral control and product knowledge are significantly related to purchase intention to buy alternative medicine; whereas attitude and subjective norm did not have significant relationship with intention to purchase alternative medicine. Perceived behavioral control and knowledge should be taken into consideration for developing marketing strategies in order to enhance patient’s intention to purchase alternative medicine.